KOGNISI DAN KREATIVITAS SEBAGAI AKTUALISASI HUMAN SELF DI ERA GENERASI Z - SUMARNI SUMARNI (Universitas Islam Negeri Mataram, 2019)
The purpose of this article is to examine how humans can process their thoughts / cognitions to become great people through the creativity they create. Because many people who have talent but are unable to cultivate their talents to become great people. This article uses the type of research based on literature studies conducted through data collection and documentation, with analytical techniques using data reduction and drawing conclusions and through literature praxis starting from books, scientific journals, e-books, the internet and various available facts, results and discussion that Cognition is a thought process that involves the work of the brain, processing information and then understanding, knowledge and gaining knowledge. From this thought process, then someone can create something new through a real work idea that is different from something that already exists. This is what is called, creativity, one's ability to create something new. So the source of one's creativity is because of the tendency of self-actualization to be developed and mature, and to realize potential, to encourage it to develop into mature.